LPS-induced serum TNF production and lethality in mice: effect of L-carnitine and some acyl-derivatives - Vito Ruggiero; Claudio M. D'Urso; Claudio Albertoni; Silvia Campo; Piero Foresta; Edoardo Arrigoni Martelli (Mediators of Inflammation)
The effect of L-carnitine and some of its acyl derivatives on serum TNF production and lethality in a murine experimental endotoxin shock model was investigated. In some instances, serum IL-6 production was also evaluated. In this experimental model, C57BL/6 mice received 30 mg/kg LPS (E. cell 055:B5) injected intraperitoneally, while L-carnitine and its derivatives were administered according to different schedules. Serum levels of TNF and IL-6 were evaluated 1 h following LPS injection. The treated animals were also monitored daily for differences in body temperature, feeding, and survival for 10 days after LPS injection. Although some derivatives were able to significantly affect TNF production, the marked decrease in serum TNF levels of LPS-treated mice was not paralleled by a substantial increase in survival.